The occlusal wear of ceramic fixed dental prostheses: 3-Year results in a randomized controlled clinical trial with split-mouth design. (December 2020) - Seidel, Anna; Belli, Renan; Breidebach, Nathalie; Wichmann, Manfred; Matta, Ragai Edward
Abstract: Objectives: This study's hypothesis was to evaluate differences of the occlusal wear rate for monolithically fabricated lithium disilicate and hand-veneered zirconia crowns in-vivo. Furthermore, a comparison of the materials' clinical performance according to CDA criteria was investigated. Methods: A total number of 15 patients in the need of full-coverage ceramic fixed dental prosthesis on molars were treated with two crowns each (n = 30), randomly assigned on the contralateral sides made of monolithic IPS e.max CAD (n = 15) and IPS e.max Ceram hand-veneered zirconia (n = 15). Clinical examination was conducted, silicone impressions were taken and plaster models fabricated at the day of crown insertion (baseline) and after 1, 2 and 3 years. The abrasion rate was digitally investigated: after model digitization with the industrial scanner Atos II, each follow-up model was superimposed with the baseline model. The wear was evaluated as the difference between two scans in terms of maximum vertical loss [mm], average decrease [mm] and volume loss [mm³]. For statistical analysis, the Mann–Whitney U test was performed and significance was set to less than 0.05. Results: IPS e.max CAD crowns showed a volume loss of −0.68 mm³ after three years, while IPS e.max Ceram hand-veneered zirconia crowns showed a volumetric wear of −0.75 mm³ at the same point of time. However, no significant differences were found between both materials regarding the 3 evaluated wear parameters. The survival rate for both materials was 100 % and the clinical performance outcome was good to excellent. Conclusion: The two investigated materials for ceramic fixed dental prostheses showed similar wear rates and clinical performance over an in-vivo use of 3 years. Clinical Significance: Ceramic restorations are subject to occlusal wear over time due to the natural masticatory process. Both monolithic lithium disilicate and glass-ceramic veneered zirconia copings showed clinically satisfactory results over 3 years in-situ. In terms of abrasion, they are equally well suited for clinical use.